TRANSFORMING EDUCATION TO PREPARE FUTURE GENERATIONS TO FACE GLOBAL CHALLENGES - Nur, Muhammad; Zamroni, Zamroni; Tamam, Badrut (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:This study aims to explore and analyze how educational transformation can prepare future generations to face increasingly complex global challenges. Using a qualitative approach, this study identifies various changes in the education system that are needed to respond to the dynamic development of the world. The research findings indicate that education should focus on strengthening 21st century skills, integrating technology into learning, and developing inclusive and adaptive character.